"\\frac{y^2}{2}+2ye^t+(y+e^t)dy\/dt=0"
"(\\frac{y^2}{2}+2ye^t)dt+(y+e^t)dy=0"
"P(t,y)=\\frac{y^2}{2}+2ye^t"
"Q(t,y)=y+e^t"
"\u2202P\/\u2202y=y+2e^t"
"\u2202Q\/\u2202t=e^t"
"\u2202P\/\u2202y \\not = \u2202Q\/\u2202t", so equation is not exact.
Let's find an integrating factor "\\mu" :
"\\xi=\\frac{\u2202P\/\u2202y - \u2202Q\/\u2202t}{Q}=\\frac{y+2e^t-e^t}{y+e^t}=\\frac{y+e^t}{y+e^t}=1"
"\\xi" is a function of t only (not y), let it be denoted by "\\xi (t)". Then
"\\mu=e^{\\int\\xi(t)dt}=e^{\\int dt}=e^t"
Differential equation with integrating factor:
"(\\frac{y^2e^t}{2}+2ye^{2t})dt+(ye^t+e^{2t})dy=0"
"P_1(t,y)=\\frac{y^2e^t}{2}+2ye^{2t}"
"Q_1(t,y)=ye^t+e^{2t}"
"\u2202P_1\/\u2202y=ye^t+2e^{2t}"
"\u2202Q_1\/\u2202t=ye^t+2e^{2t}"
"\u2202P_1\/\u2202y = \u2202Q_1\/\u2202t", so equation "(\\frac{y^2e^t}{2}+2ye^{2t})dt+(ye^t+e^{2t})dy=0" is exact.
So, solution of this equation "f(t,y)" and "\u2202f(t,y)\/\u2202t=P_1(t,y)" and "\u2202f(t,y)\/\u2202y=Q_1(t,y)".
"f(t,y)=\\int P_1(t,y)dt +\\phi(y)"
"f(t,y)=\\int (\\frac{y^2e^t}{2}+2ye^{2t})dt +\\phi(y)=\\frac{y^2e^t}{2}+ye^{2t} +\\phi(y)"
"\u2202f(t,y)\/\u2202y=(\\frac{y^2e^t}{2}+ye^{2t} +\\phi(y))'=ye^{t}+e^{2t}+\\phi'(y) =Q_1(t,y)"
"ye^{t}+e^{2t}+\\phi'(y) =ye^t+e^{2t}"
"\\phi'(y) =0"
"\\phi(y) =C_1"
"f(t,y)=\\frac{y^2e^t}{2}+ye^{2t} +C_1"
So, a solution of the differential equation is
"f(t,y)=C_2"
"\\frac{y^2e^t}{2}+ye^{2t} +C_1=C_2,\\, C=C_2-C_1,"
"\\frac{y^2e^t}{2}+ye^{2t} =C"
Answer: "\\frac{y^2e^t}{2}+ye^{2t} =C"
Comments
Leave a comment